2015
DOI: 10.17509/edusentris.v2i2.165
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Kemampuan Membaca Kritis Dalam Pembelajaran Penemuan Dan Kemampuan Berpikir Kritis Siswa

Abstract: Penelitian ini bertujuan untuk mendeskripsikan hubungan antara kemampuan membaca kritis bacaan sains yang disisipkan dalam pembelajaran energi di kelas dengan keterampilan berpikir kritis siswa sebagai keterampilan yang dituntut pada abad 21. Metode penelitian yang digunakan adalah penelitian korelasional (deskriptif). Populasi pada penelitian ini adalah siswa kelas VII pada salah satu SMP di Kota Cimahi dengan sampel penelitian sebanyak 35 siswa kelas VII tahun pelajaran 2014-2015. Kegiatan membaca kritis dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…In comparison, this integration aspect is part of a high level of thinking ability that combines new information and knowledge that has been possessed to build and connect further information (Priyatni, & Nurhadi., 2017). Nevertheless, when noted, this happens because reading habituation can stimulate high-level thinking ability and affect learning outcomes (Muttaqiin & Sopandi, 2015). Therefore, learners can form a broad understanding of the readings presented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, this integration aspect is part of a high level of thinking ability that combines new information and knowledge that has been possessed to build and connect further information (Priyatni, & Nurhadi., 2017). Nevertheless, when noted, this happens because reading habituation can stimulate high-level thinking ability and affect learning outcomes (Muttaqiin & Sopandi, 2015). Therefore, learners can form a broad understanding of the readings presented.…”
Section: Discussionmentioning
confidence: 99%
“…Although this indicator is considered the most difficult, if the learner has good literacy through habituation and fondness for reading, it can improve the ability to think highly in evaluating a text. According to Archambault (Muttaqiin & Sopandi, 2015), contextual readings have an advantage because these types of readings contain a certain amount of information related to experience. Pisa's question in this indicator also measures what is already known by what learners can do from their knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, research showed that there was a significant positive relationship between reading and critical thinking; critical reading skills will help students to practice critical thinking. In order to understand the whole information given, the students will think critically while analyzing and evaluating text in the process of reading [8]. After successfully getting the information, they will take a side and make contradictions for testing the validity of the information, whether it is suitable for the current situation.…”
Section: Critically Literacymentioning
confidence: 99%
“…Several studies have shown that reading skills have a relevant relationship with critical thinking (Sariyem, 2016;Muttaqiin, 2015). Therefore, the selection of learning methods needs to pay attention to the level of the students' critical thinking.…”
Section: Introductionmentioning
confidence: 99%